Design And Implementation Of An End-To-End Simulator For The BepiColombo Rotation Experiment - Palli, Alessandra <1983> (Alma Mater Studiorum - Università di Bologna, 2012)
Among the scientific objectives addressed by the Radio Science Experiment hosted on board the ESA mission BepiColombo is the retrieval of the rotational state of planet Mercury. In fact, the estimation of the obliquity and the librations amplitude were proven to be fundamental for constraining the interior composition of Mercury. This is accomplished by the Mercury Orbiter Radio science Experiment (MORE) via a strict interaction among different payloads thus making the experiment particularly challenging. The underlying idea consists in capturing images of the same landmark on the surface of the planet in different epochs in order to observe a displacement of the identified features with respect to a nominal rotation which allows to estimate the rotational parameters. Observations must be planned accurately in order to obtain image pairs carrying the highest information content for the following estimation process. This is not a trivial task especially in light of the several dynamical constraints involved. Another delicate issue is represented by the pattern matching process between image pairs for which the lowest correlation errors are desired. The research activity was conducted in the frame of the MORE rotation experiment and addressed the design and implementation of an end-to-end simulator of the experiment with the final objective of establishing an optimal science planning of the observations. In the thesis, the implementation of the singular modules forming the simulator is illustrated along with the simulations performed. The results obtained from the preliminary release of the optimization algorithm are finally presented although the software implemented is only at a preliminary release and will be improved and refined in the future also taking into account the developments of the mission.